O uso das ferramentas de marketing digital para a venda de cursos online por empresas de pequeno e médio porte - Alexandre Cesar Machado, Osello (2023)
This study aims to analyze how small and medium-sized companies are using digital marketing tools to sell online courses. The theoretical review covers Digital Marketing, Infoproducts, Small and Medium-sized Companies. Through exploratory qualitative research with eight in-depth interviews with producers, affiliates and consumers of infoproducts, we developed further knowledge about the use of these tools in selling online courses. The results helped create a map with an integrated set of digital marketing tools that enable better performance by companies marketing online courses. This study contributes with an innovative theoretical approach to a current, relevant topic in business practice. As managerial contributions, companies in this sector are presented tools that can leverage financial growth.